Unraveling the Molecular Basis of Seed Viability and Longevity through Integrated Proteomic and Metabolomic Approaches - Singh, Sultan; Bharti, Akhil; Singh, Jasdev; Gulzar, Iram; Singh, Jagdeep; Kamboj, Mohit; Singh, Vikram (International Journal of Bio-resource and Stress Management, 2025)
This review considered the key factors that regulated seed viability, including environmental conditions and genetic effects and the molecular processes involved during seed storage and germination. Proteomics and metabolomics were key technologies for investigating the molecular properties of seed biology and clarify the mechanisms underlying seed longevity. It underlined the importance of regulatory networks and signaling pathways in seed survival determination. Proteomics employs methodologies like 2D-PAGE and LC-MS/MS to detect stress-responsive proteins and storage proteins that altered with age and desiccation. Metabolomic profiling on GC-MS, LC-MS and NMR explained the roles of primary and secondary metabolites, including antioxidants, sugars and lipids, in seed longevity. Multi-omics approaches gave a deep understanding of seed viability through proteomics and metabolomics combined together, as evidenced by case studies that highlighted the benefits of this integrative method. This review examined storage conditions such as temperature, moisture and availability of oxygen levels on seed proteins and metabolites and the role of desiccation and subsequent rehydration towards seed viability. It examined species-level variations in proteomic and metabolomic profiles among different crop seeds, with a special focus on new adaptations in short-lived or high-value species. In addition, the capacity of proteomics and metabolomics in generating seeds with longer lifespans and the establishment of molecular markers to determine seed quality was addressed. The advent of new technologies and the combination of genomics and transcriptomics promise to further accelerate our knowledge and applications in precision agriculture and food security. Regardless of data interpretation problems, such advances offered great prospects for enhancing seed quality and crop yields.